Czech drama during the protectorate - Janoušek, Pavel (Bohemica Olomucensia, 2019)
This text is a draft of a chapter from the upcoming publication History of Czech literature in Protectorate of Bohemia and Moravia, prepared by the collective of authors under the leading of Pavel Janoušek a funded by the grant project GA ČR 18-14478S. Shortened and modified versions of already published studies "Alegorie o moru, hříchu, společnosti, duši, trestu a oběti" (in Pavel Janoušek: ... a další studie, Academia 2018) a "Hry o požáru" are part of this text, too. The author of the subchapter about František Zavřel is Eduard Burget.
Keywords: poetics of drama; allegorical drama; historical drama